DETERMINATION OF MISCONCEPTIONS ABOUT MASS AND WEIGHT OF 7TH GRADE STUDENTS OF MIDDLE SCHOOL - Doğanay, Kamil (Bahattin AYDINLI, 2020)
The aim of this study is to determinemisconceptions about the mass and weight of 7th grade students. The study wasconducted in the fall semester of 2019-2020 in a public school in Kastamonu.The universe of the study consists of all seventh grade students in Kastamonuprovince. The research sample of the study consists of seventh grade studentsconsisting of 20 people in a public school determined by random sampling. Theresearch method, which is one of the quantitative research methods, was used.In the study, a 3-stage achievement test consisting of 10 questions developedby the researcher was used as data collection tool. The findings obtained inthe study were subjected to descriptive statistics. As a result of theresearch, misconceptions of the students were determined and suggestions weremade.
Keywords: Science; misconception; mass and weight; 4. Education